Glyphosate Hormesis Improves Agronomic Characteristics and Yield of Glyphosate-Resistant Soybean Under Field Conditions - Krenchinski, Fábio Henrique [UNESP]; Pereira, Vinicius Gabriel Canepelle [UNESP]; Giovanelli, Bruno Flaibam [UNESP]; Cesco, Victor José Salomão [UNESP]; Alcántara-de la Cruz, Ricardo [UNESP]; Velini, Edivaldo D. [UNESP]; Carbonari, Caio A. [UNESP] (MDPI, 2024)
Brazil, the world’s largest soybean producer, owes its success to the cultivation of glyphosate-resistant (GR) cultivars. However, the soybean yields lag behind those obtained in areas managed for high productivity. Glyphosate-induced hormesis holds promise for increasing crop yields, but the potential evolution of resistance in certain weed species poses a challenge to foliar applications under field conditions. This study assessed the effects of a hormesis-inducing glyphosate dose [90 g acid equivalent (ae) ha−1] on the agronomic characteristics and yield of four GR soybean cultivars. The evaluation was conducted in field settings across various Brazilian locations, considering foliar, seed, and seed + foliar treatments. The results showed variations in dry mass, root nodules, nutrient composition, plant height, pods, and yield, primarily influenced by environmental conditions, soil quality, and, ultimately, the interaction between GR cultivars and treatments. Total dry mass consistently increased with glyphosate, with seed and seed + foliar treatments showing the most substantial increases (7–21%). All three treatments increased nodulation by up to 36% across locations and cultivars, with seed + foliar treatment causing notable increases in nodule dry mass (up to 56%), followed by seed treatment (41%). Nutrient composition, especially for N, P, Br, and Fe, displayed location-dependent variations. Plant height varied among locations and cultivars, with minimal differences between treatments. Glyphosate treatments increased pod numbers (10 to 35%) and yields (11 to 42%) of soybean in seed and seed + foliar treatments. The findings highlight the potential of glyphosate hormesis as a viable tool for improving yields of GR soybean cultivars at the field level. However, the extent of benefits depends on the agronomic conditions of location, choice of cultivars, and herbicide application method.
Keywords: foliar applications; Glycine max; herbicide; nutritional composition; seed treatment